2020
DOI: 10.1021/acsami.0c02328
|View full text |Cite
|
Sign up to set email alerts
|

Flexoelectricity in Flexoionic Polymer Electrolyte Membranes: Effect of Thiosiloxane Modification on Poly(ethylene glycol) Diacrylate and Ionic Liquid Electrolyte Composites

Abstract: The present article entails the generation of flexoelectricity during cantilever bending of a solid polymer electrolyte membrane (PEM), composed of poly­(ethylene glycol) diacrylate (PEGDA) precursor and ionic liquid (hexylmethyl­imidazolium hexafluorophosphate). The effects of thiosiloxane modification of PEGDA precursor on glass transition, ionic conductivity, and flexoelectric performance have been explored as a function of PEM composition. The glass transition temperature (T g) of the PEM declines with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 29 publications
(51 reference statements)
8
29
1
Order By: Relevance
“…It appears that the cells cross-linked in the isotropic phase, and those that are cross-linked in the nematic phase between planar alignment substrates, give the largest response with flexo-ionic coefficients . Such coefficients are comparable to the well-developed iEAPs (see Table 1 ) [ 6 , 9 ]. It is interesting to discern that the flexo-ionic coefficients of iLCEs outperform the flexoelectric (polarization mechanism is different) coefficients of ceramics (PZT [ 12 ] and Ba 0.67 Sr 0.33 TiO 3 [ 40 ]), crystalline polymers (PVDF) [ 41 ], and bent-core liquid crystals [ 18 , 19 ] as indicated in Table 1 .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It appears that the cells cross-linked in the isotropic phase, and those that are cross-linked in the nematic phase between planar alignment substrates, give the largest response with flexo-ionic coefficients . Such coefficients are comparable to the well-developed iEAPs (see Table 1 ) [ 6 , 9 ]. It is interesting to discern that the flexo-ionic coefficients of iLCEs outperform the flexoelectric (polarization mechanism is different) coefficients of ceramics (PZT [ 12 ] and Ba 0.67 Sr 0.33 TiO 3 [ 40 ]), crystalline polymers (PVDF) [ 41 ], and bent-core liquid crystals [ 18 , 19 ] as indicated in Table 1 .…”
Section: Discussionsupporting
confidence: 69%
“…The past few decades have witnessed a flourishing development of electro-mechanical transducers for use in soft robotics [1][2][3], sensors [4,5] and micropower generations [6][7][8][9]. Piezoelectricity and flexoelectricity are the two major physical mechanisms for linear electro-mechanical transduction for insulating materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies also reported the benefits of solidstate electrolyte membranes in LIBs [34,35] and energy harvesting from mechanical deformation. [36][37][38] The present work is built on the early concepts of Raut et al [33] to alleviate the concerns of loss of IL from the ionogel membranes at high temperature due to differences in thermal expansion coefficient of solid strands in sPS gel and the liquid state IL. In this context, the threedimensional δ-form sPS porous gels [39,40] offered higher melting temperature (275 C C) and dimensional stability at high temperature compared to commercial polyolefin membranes, such as polyethylene and polypropylene, with melting temperature, respectively, 135 and 160 C. [41,42] The loss of IL from the ionogel membrane at high temperature was avoided in this work by using a polymerizable IL (PIL) and 1-ethyl-3-vinylimidazolium bis (trifluoromethylsulfonyl) imide (VI-TFSI).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies also reported the benefits of solid‐state electrolyte membranes in LIBs [ 34,35 ] and energy harvesting from mechanical deformation. [ 36–38 ]…”
Section: Introductionmentioning
confidence: 99%